Equity in access to health care among asylum seekers in Germany: evidence from an exploratory population-based cross-sectional study - Bozorgmehr, Kayvan; Tunkl, Christine; Joos, Stefanie (BMC health services research, 2015)
Research on inequities in access to health care among asylum-seekers has focused on disparities between asylum-seekers and resident populations, but little attention has been paid to potential inequities in access to care within the group of asylum-seekers. We aimed to analyse the principles of horizontal equity (i.e., equal access for equal need irrespective of socioeconomic status, SES) and vertical equity (higher allocation of resources to those with higher need) among asylum-seekers in Germany.